Analysis of stress response distribution in patients with lateral ankle ligament injuries: a study of neural control strategies utilizing predictive computing models - Zhou, Zhifeng; Zhou, Huiyu; Jie, Tianle; Xu, Datao; Teo, Ee-Chon; Wang, Meizi; Gu, Yaodong (Frontiers in Physiology, 2024)
Background: Ankle sprains are prevalent in sports, often causing complex injuries to the lateral ligaments. Among these, anterior talofibular ligament (ATFL) injuries constitute 85%, and calcaneofibular ligament (CFL) injuries comprise 35%. Despite conservative treatment, some ankle sprain patients develop chronic lateral ankle instability (CLAI). Thus, this study aimed to investigate stress response and neural control alterations during landing in lateral ankle ligament injury patients.Method: This study recruited twenty individuals from a Healthy group and twenty CLAI patients performed a landing task using relevant instruments to collect biomechanical data. The study constructed a finite element (FE) foot model to examine stress responses in the presence of laxity of the lateral ankle ligaments. The lateral ankle ligament was modeled as a hyperelastic composite structure with a refined representation of collagen bundles and ligament laxity was simulated by adjusting material parameters. Finally, the validity of the finite element model is verified by a highspeed dual fluoroscopic imaging system (DFIS).Result: CLAI patients exhibited earlier Vastus medialis (p<0.001) and tibialis anterior (p<0.001) muscle activation during landing. The FE analysis revealed that with laxity in the ATFL, the peak von Mises stress in the fifth metatarsal was 20.74 MPa, while with laxity in the CFL, it was 17.52 MPa. However, when both ligaments were relaxed simultaneously, the peak von Mises stress surged to 21.93 MPa. When the ATFL exhibits laxity, the CFL is subjected to a higher stress of 3.84 MPa. Conversely, when the CFL displays laxity, the ATFL experiences a peak von Mises stress of 2.34 MPa.This study found that changes in the laxity of the ATFL and the CFL are linked to shifts in metatarsal stress levels, potentially affecting ankle joint stability. These alterations may contribute to the progression towards CLAI in individuals with posterolateral ankle ligament injuries. Additionally, significant muscle activation pattern changes were observed in CLAI patients, suggesting altered neural control strategies post-ankle ligament injury.